GAMBARAN PERILAKU HIDUP BERSIH DAN SEHAT (PHBS) DI DESA CITTA KECAMATAN CITTA KABUPATEN SOPPENG - Srisartita Srisartita; Muhammad Akhyar Ahmad (-, 2022)
ABSTRACT Clean and healthy behavior is a set of behaviors that are based on awareness as a result of learning that makes a person or family in the field of health can help themselves and realize personal and family health by playing an active role,. Implementation of clean and healthy living behavior in the household is the responsibility of the household.In this research type with descriptive research method. In this study with the population are all families in Bakalan Village Wayut Village Jiwan District as many as 805 families, with a large sample of 267 families. In this research using Quota Sampling method. Quota sampling is a method whereby any member of the population can be met. Sample criteria in this study are families with school children, families with pregnat women and families with postpartum mothers.The result of this research is 72 familiy leaders (27%) with households that have clean and healthy life behavior and do not have clean and healthy life behavior as much as 195 family leaders (73%), delivery aid is done by 100%. A family that exclusively breastfeeding as much as 74%, excluding breast milk exclusively by 26%, weighing infants and children less than five years regularly is 90% and those who do not weighing regularly as much as 10%, respondents who wash hands with water and soap as much as 94%, and that do not do handwashing with soap and water 6%, in this research all respondents use clean water 100%. Respondents who use healthy latrine as much 96% and who do not use healthy latrine as much 4%, result of this research got 83% free house larvae, result of research Ian about consuming fruits and vegetables everyday as much as 96% and who do not consume fruits and vegetables as much as 4%, the results of research on physical activity everyday as much as 90%, who do not smoke in the house as much as 28%. Smoking in the home as much as 72%.It is expected that the health personnel will always improve the health service to the community, especially about the activities of clean and healthy life and is expected to the family to always increase their knowledge so as to be able to carry out the activities of clean and healthy life in everyday. Keywords: family, clean and healthy live behavior, household ABSTRAKGAMBARAN PERILAKU HIDUP BERSIH DAN SEHAT DI DESA CITTA KECAMATAN CITTA KABUPATEN SOPPENG Perilaku hidup bersih dan sehat adalah sekumpulan perilaku yang dilakukan berdasarkan atas kesadaran sebagai hasil pembelajaran yang menjadikan seseorang atau keluarga dapat menolong diri sendiri dalam bidang kesehatan dan berperan aktif dalam  mewujudkan kesehatan pribadi dan keluarga. Penerapan PHBS di rumah tangga merupakan tanggung  jawab setiap anggota rumah tangga.Jenis penelitian yang digunakan adalah metode deskriptif. Populasinya adalah semua keluarga di desa CittaKecamatan Citta sebanyak 805 KK, dengan besar sampel 267 KK. Metode yang digunakan adalah Quota sampling : yaitu anggota populasi manapun yang penting memenuhi quotum terpenuhi. Kriteria sampel penelitian ini adalah keluarga dengan anak sekolah, keluarga dengan ibu hamil dan keluarga dengan ibu nifas.Hasil penelitian diperoleh 72 KK (27%) dengan rumah tangga ber-PHBS dan tidak ber-PHBS 195 KK (73%), pertolongan persalinan seluruhnya oleh tenaga kesehatan 100%, memberikan ASI eksklusif 197 KK (74%) , tidak ASI eksklusif 26%, penimbangan bayi dan balita secara rutin  90% dan tidak penimbangan rutin 10%, melakukan cuci tangan menggunakan air dan sabun  94%, tidak melakukan cuci tangan menggunakan air dan sabun 6%, seluruhnya menggunakan air bersih 100%, menggunakan  jamban sehat 96%, tidak menggunakan jamban sehat 4%, rumah bebas jentik 83% ,rumah tidak bebas jentik 17%, mengkonsumsi buah dan sayur setiap hari 96%, tidak mengkonsusi buah dan sayur 4%, melakukan aktifitas fisik 90%, tidak melakukan aktifitas fisk 10%, tidak merokok dalam rumah 28%, dan yang merokok dalam rumah 72%.Tenaga kesehatan diharapkan senantiasa meningkatkan pelayanan kesehatan masyarakat terutamamengenai kegiatan PHBS dan keluarga diharapkan senantiasa menambah pengetahuan sehingga mampu melaksanakanPHBS sehari-hari.  Kata kunci: keluarga, perilaku hidup bersih dan sehat, rumah tangga